Cardiovascular health control in the family health strategy - Tavares, Gilberto Andrade; Ribeiro, Joathan Borges; Almeida-Santos, Marcos Antonio; Sousa, Antônio Carlos Sobral; Barreto-Filho, José Augusto Soares (Frontiers in Cardiovascular Medicine, 2022)
Introduction In Brazil, the Unified Health System (SUS) controls and oversees public health care, and the Family Health Strategy (FHS) is its primary access, with 60% of the population registered in it. The surveillance of risk factors for cardiovascular diseases (CVD) is the responsibility of the FHS. In 2010, the American Heart Association (AHA) proposed the evaluation of seven metrics (smoking, Body Mass Index (BMI), physical activity, diet, total cholesterol, blood pressure and blood glucose) with an aim to monitoring cardiovascular health (CVH). However, the results of the FHS regarding the CVH of the Brazilian population are unascertained. Objective Evaluate the control of CVH among adult patients treated by the FHS in the city of Aracaju, Sergipe, Brazil. Material and methods A cross-sectional study was conducted using the seven metrics recommended by the AHA to evaluate CVH among patients treated by the FHS. The city of Aracaju has a population of 571,149 inhabitants, with 394,267 > 20 years of age; therefore, it was admitted that in a simple random sample, sampling error of 5% with 95% CI, 329 individuals would be needed. Results Among 400 patients, only 32.5% had controlled CVH. In a univariate analysis, the adjusted multivariate analysis found that being female (aOR: 2.07 IC: 1.20 to 3.60 p: 0.006) under 45 years old (aOR: 1.61 IC: 1.15 to 2.28 p: 0.006) and with the habit of following health advice from family members and neighbors (aOR: 1.28 IC: 1.15 to 2.28 p: 0.040) were associated with control of CVH. On the other hand, those ones who had a greater number of children (aOR: 0.91 IC: 0.84 to 0.95 p: 0.020) were associated with less control of CVH. Conclusions The study showed that only 32.5% of patients have controlled CVH. Being a woman, young and following health advice from family members and neighbors have a positive influence in controlling CVH. More children reduced controlling these metrics.